"Todas las voces que me hablan simultáneamente": Anzaldúa’s Voice from the Borderlands - Alves Lobo, Patrícia (Complutense Journal of English Studies, 2015)
This article analyses how Anzaldúa uses language intersections to underline the hybridity of Chicano women in Borderlands/La Frontera: The New Mestiza (1987). It starts by reflecting on how Anzaldúa exposes the use of language as a source of segregation and bias in the dominant society, as well as among Chicanos themselves, as the author reveals a connection between linguistic oppression and patriarchal values. Then it focuses on the way Anzaldúa uses language in her work in order to validate her own experience between worlds and to induce a social paradigm shift, by the deconstruction of preestablished dogmas and confrontation with alterity. Different languages in this work convey a parallel message to the content of the text, proving not only that language barriers can be converted into a fluid space of inclusion, but also that the U.S. reality incorporates the sounds and voices of minority groups often ignored and oppressed, sounds and voices which are in themselves an U.S. idiosyncrasy. Borderlands/La Frontera: The New Mestiza announces that the future depends on the disruption of fixed paradigms and must be built beyond borders, acknowledging the hybrid identity together with the resulting hybrid linguistic expression.